1999
DOI: 10.1107/s0909049598018202
|View full text |Cite
|
Sign up to set email alerts
|

XAFS Debye–Waller factors in aqueous Cr+3 from molecular dynamics

Abstract: Controversy exists on whether the second hydration shell of the aqueous chromium +3 cation is observable by XAFS. The problem is aggravated by strong first shell multiple scattering contributions competing with the second hydration shell signal. By finding ab initio values for nearly all free parameters in the theory, we greatly reduce the number of parameters to be fit, thus allowing an unambiguous resolution of this controversy. Quantum chemistry calculations yielded a parameterized force field model which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 10 publications
2
53
0
Order By: Relevance
“…14 and 16͒, are required to shed light on this point, as already shown in the XAS study of other single ions. 27,28,[51][52][53][54][55] Related to these XANES computations, a further point to be investigated is the analysis of the efficiency of the FMS approach when the asymmetric structures, resulting from the fluxional behavior of the aquaion and its close environment, were considered to provide an average spectrum. The efficiency of alternative methods, such as finite-difference method, 56 should be explored.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…14 and 16͒, are required to shed light on this point, as already shown in the XAS study of other single ions. 27,28,[51][52][53][54][55] Related to these XANES computations, a further point to be investigated is the analysis of the efficiency of the FMS approach when the asymmetric structures, resulting from the fluxional behavior of the aquaion and its close environment, were considered to provide an average spectrum. The efficiency of alternative methods, such as finite-difference method, 56 should be explored.…”
Section: Figmentioning
confidence: 99%
“…We believe that the spectroscopical peculiarities associated to the double channel appearing in the ionization pro- cess of the Cu͑II͒ hydrate in water provide a fairly good background to further XAS molecular-dynamics combined studies. 27,28,[51][52][53][54][55] Thus, the microscopic representation of the dynamics of this hydration would allow the computation of simulated EXAFS and XANES spectra from a statistically significant set of structures, and then to extract additional conclusions about the relative importance of the different structures contributing to the XAS spectra, the doublechannel spectroscopic peculiarity being simultaneously considered.…”
Section: Figmentioning
confidence: 99%
“…Unfortunately, there is a difficulty in regard to the inclusions of hydrogen atoms in the FEFF code. 6,21,26,27 This difficulty exists because the O-H bond is much shorter than the Pd-O distance, and for the oxygen and hydrogen it is difficult to determine a good muffin-tin radius: FEFF code gives unrealistic muffin-tin radii and an overestimation of the backscattering contribution. 21,26,27 Here, to resolve this problem, we have used a known approximation by substituting the backscatter with the next chemical element.…”
Section: Xafs Analysis Of Pd(ii) Aqua Ion In Pure Perchlorate Solutiomentioning
confidence: 99%
“…The problem is usually explained by strong first-shell MS contributions competing with the second hydration shell signal. 27,[29][30][31] Also, in the simplest case, as octahedral aqua ions (Cr 3+ and Zn 2+ ), controversy exists. For example, in the recent paper of Campel et al is reported that the second shell of Cr 3+ is responsible only for about 1/3 of the XAFS FT signal at the position of the second shell.…”
Section: Xafs Analysis Of Pd(ii) Aqua Ion In Pure Perchlorate Solutiomentioning
confidence: 99%
“…Although in several articles EXAFS spectra have been generated based on MD structural data, 11,12 only a preliminary investigation in the XANES region has been published, to the best of our knowledge. 13 Up to now, the calculation of these spectra was based on the assumption of a single structure.…”
Section: Introductionmentioning
confidence: 99%